Towards equity: a retrospective analysis of public sector radiological resources and utilization patterns in the metropolitan and rural areas of the Western Cape Province of South Africa in 2017 - Beulah Christina van Zyl; Michelle Monique Barnard; Keith Cloete; Amanda Fernandez; Matodzi Mukosi; Richard Denys Pitcher (BMC, 2021)
Abstract Background The reduction of inequality is a key United Nations 2030 Sustainable Development Goal (WHO, Human Resources for Health: foundation for Universal Health Coverage and the post-2015 development agenda, 2014; Transforming our world: the 2030 Agenda for Sustainable Development .:. Sustainable Development Knowledge Platform, 2020). Despite marked disparities in radiological services globally, particularly between metropolitan and rural populations in low- and middle-income countries, there has been little work on imaging resources and utilization patterns in any setting (Transforming our world: the 2030 Agenda for Sustainable Development .:. Sustainable Development Knowledge Platform, 2020; WHO, Local Production and Technology Transfer to Increase Access to Medical Devices, 2019; European Society of Radiology (ESR), Insights Imaging 6:573-7, 2015; Maboreke et al., An audit of licensed Zimbabwean radiology equipment resources as a measure of healthcare access and equity, 2020; Kabongo et al., Pan Afr Med J 22, 2015; Skedgel et al., Med Decis Making 35:94-105, 2015; Mollura et al., J Am Coll Radiol 913-9, 2014; Culp et al., J Am Coll Radiol 12:475-80, 2015; Mbewe et al., An audit of licenced Zambian diagnostic imaging equipment and personnel, 2020). To achieve equity, a better understanding of the integral components of the so called "imaging enterprise" is important. The aim was to analyse a provincial radiological service in a middle-income country. Methods An institutional review board-approved retrospective audit of radiological data for the public healthcare sector of the Western Cape Province of South Africa for 2017, utilizing provincial databases. We conducted population-based analyses of imaging equipment, personnel, and service utilization data for the whole province, the metropolitan and the rural areas. Results Metropolitan population density exceeds rural by a factor of ninety (1682 vs 19 people/km2). Rural imaging facilities by population are double the metropolitan (20 vs 11/106 people). Metropolitan imaging personnel by population (112 vs 53/106 people) and equipment unit (1.7 vs 0.7/unit) are more than double the rural. Overall population-based utilization of imaging services was 30% higher in the metropole (289 vs 214 studies/103 people), with mammography (24 vs 5 studies/103 woman > 40 years) and CT (21 vs 6/103 people) recording the highest, and plain radiography (203 vs 171/103 people) the lowest differences. Conclusion Despite attempts to achieve imaging equity through the provision of increased facilities/million people in the rural areas, differential utilization patterns persist. The achievement of equity must be seen as a process involving incremental improvements and iterative analyses that define progress towards the goal.